2021
DOI: 10.18203/2349-3291.ijcp20212053
|View full text |Cite
|
Sign up to set email alerts
|

Kangaroo mother care in COVID-19 pandemic, accepting the new normal

Abstract: Background: Kangaroo mother care is an evidence-based, low cost and high impact approach that has shown significant reduction in preterm mortality. Practising KMC in COVID 19 era, is a challenge for mothers and the NICU’s. Aim of the study was to assess the effect of this pandemic on the practice of KMC in our NICU and opine about the possible barriers.Methods: It was a retrospective observational cohort study. Data was collected from the NICU records. Neonates fulfilling the inclusion criteria were classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…11 Few studies have explored the effect of Covid-19 among mothers practicing KMC particularly in low-and middle-income countries with reports of reduction in KMC practices in limited resource settings. 10,12 Studies that aimed at improving the quality of KMC and overcoming barriers to KMC during the pandemic period found that homegrown solutions and strategies by mothers and healthcare workers could have more ownership and are likely to be more sustainable. 13,14 Partners and family members often play a big role in decision-making regarding KMC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Few studies have explored the effect of Covid-19 among mothers practicing KMC particularly in low-and middle-income countries with reports of reduction in KMC practices in limited resource settings. 10,12 Studies that aimed at improving the quality of KMC and overcoming barriers to KMC during the pandemic period found that homegrown solutions and strategies by mothers and healthcare workers could have more ownership and are likely to be more sustainable. 13,14 Partners and family members often play a big role in decision-making regarding KMC.…”
Section: Introductionmentioning
confidence: 99%
“…11 Few studies have explored the effect of Covid-19 among mothers practicing KMC particularly in low- and middle-income countries with reports of reduction in KMC practices in limited resource settings. 10,12…”
Section: Introductionmentioning
confidence: 99%